The Illumination of the Lunar Disc in 1 En. 78:6-8 in Relation to the Lunar Month - Drawnel, Henryk (Revue de Qumran, 2025)
The article analyzes the Ethiopic text of 1 En. 78:6-9, in light of the Aramaic fragmentary text 4Q210 1 III, 3-8. This text overlaps with the Enochic verses and adds new information, particularly regarding the waning phase presented in detail in 1 En. 78:8. I argue that the description of the waxing of the moon in 1 En. 78:6-9 is not a summary of 4Q208-4Q209, as some scholars have suggested. Rather, it is an account of the lunar month that describes the illumination of the lunar disc and establishes its governing principle of arithmetical progression. Thus, although the 0.5/7 fraction is presented as the underlying principle of the calculation, both the Ethiopic pericope and the Aramaic text refer exclusively to the illumination of the lunar disc, as is the case with column F in 4Q208-4Q209. Any reference to lunar visibility periods, which are also governed by the 0.5/7 fraction in 4Q208-4Q209, has been omitted. Additionally, I propose a new solution to the question of the fifteen parts of lunar illumination during the waxing phase in 1 En. 78:7. Furthermore, I interpret the decrease in lunar illumination in 1 En. 78:8 as a calculation based on unit fractions, unlike in 1 En. 78:6-7 and 4Q208-4Q209.